The new tribe Fourraeeae (Brassicaceae) and two Moroccan Arabis species transferred to the new genus Hurkaea - Koch, Marcus; Karl, Robert; Al-Shehbaz, Ihsan A.; German, Dmitry A. (Phytotaxa, 2022)
The taxonomic limits of two Moroccan Arabis species are revised based on a critical evaluation of morphology in light of phylogenetic and cytogenetic studies that also included the monospecific European Fourraea. As a result, the new tribe Fourraeeae, the new genus Hurkaea and new combinations H. josiae, H. conringioides, and H. conringioides subsp. humbertii are proposed. Keys to distinguish genera, species and subspecies are provided.
Gesehen am 20.05.2022